Zmiany w biurokracji - Chrisidu-Budnik Agnieszka (Changes in the bureaucracy, 2006)
The article focuses on context of change in bureaucracy. Taking into account that bureaucracy play the major role in the modemizational and developmental processes, the analyses and characteristics included in the article are concentrated on the diagnosis of the internal conditions of the change in public institution. Authoress catalogued the faults of bureaucracy and the problems they caused. Bureaucracy is defined as a hierarchical public organization relying upon formal authority and rules to govern the activities of the members of the organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 202-209